Aplicación de un programa educativo de residuos sólidos para el fortalecimiento de capacidades ambientales de estudiantes de la I.E Sagrado Corazón de Jesús - Aguilar Sánchez, Elmer (2011)
profile, such as; diagnostics, monitoring and evaluation of knowledge and solid wastemanagement, generated in the educational institution, being fulfilled in an efficient way by the development of the programmed activities, we used practica} methods of teaching with instructional materials oriented environmental management of these suitable to our reality, dynamic, games, among others; with the objective of facilitating and strengthening the capacities of understanding, also in the students environmental awareness by encouraging participation in activities for environmental improvement and the development oftheir institution and community. W orking with 16 students between fifth and sixth grade of Primary Education, which was attended by on a regular basis during the time of execution of the project. In agreement to the results obtained on having initiated the project, the students of the educational institution, they had knowledge general relating to what they are the solid residues, so much in the concepts, problems and what to do with the solid residues. According to the results we were able to determine that the leaming of concepts in the initial evaluation, at a scale of 0-ll and ll-13, are achieving 37% and 50 %, respectively, and knowledge in the fmal evaluation of the program on a scale of 11-13 and 14-17, achieved a 93.73 % and 73.6 %, respectively ofleaming, with regard to the management and monitoring ofthe solid waste, in the fmal evaluation, ata scale of0-11 and ll-13, achieved a 56.25 % and 47.56 %, of knowledge, respectively, in the fmal evaluation to a scale of 11-13 and 14-17 are achieving 50% and 3 7.5 %, an increase of their knowledge, respectively, and toa 0-ll scale and ll-13, achieved a 62.25 % and 37.5 %, respectively, andona scale of ll-13 and 14-17, achieved a 62.25% and 31.25 %, with respect to the strengthening of capacities. In this way it is observed that the qualifications of the students it has increased as the activities were developing, since it was demonstrated in the test of hypothesis. The application of the educational program of solid residues, it strengthened his environmental capacities of the students of the Jesus Sacred Heart educational institution of the Calzadadistrict. Key words: educational institution,solid waste management